Ūniśa śatake Ḍhākāra thiẏeṭāra - Mamoon, Muntassir, 1951- (Bāṃlādeśa Śilpakalā Ekāḍemī, 1979)
History of the theater in Dacca during the nineteenth century; includes a bibliography of noted plays of the day and newspaper excerpts covering the sociocultural life of the City and a reportage about the dramatic societies and their program performances.